CREATING HISTORY: USM EXPLORES DARK ZONE OF TEMENGGOR LAKE - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, August 2015 – Universiti Sains Malaysia (USM) is going to create history for the first time in exploring the deep and dark zone of Temenggor Lake, Perak in the near future.